C−H Functionalization of Commodity Polymers. Issue 26 (26th March 2019) - Williamson, Jill B.; Lewis, Sally E.; Johnson, Robert R.; Manning, Irene M.; Leibfarth, Frank A.
Abstract: Synthetic manipulation of polymer substrates is one of the oldest and most reliable methods to increase the functional diversity of soft materials. Modifying the chemical structure of polymers that are already produced on a commodity scale leverages the current high‐volume and low‐cost production of commodity plastics for the discovery of modern materials. A myriad of polymer C−H functionalization methods have been developed which enable the modification of material properties on both a laboratory and industrial scale. More recently, driven by advances in C−H activation, photoredox catalysis, and radical chemistry, chemoselective approaches have emerged as a means to impart precise functionality onto commodity polymer substrates. This Review discusses the historical significance of and contemporary advances in the C−H functionalization of commodity polymers. The conceptual approach outlined herein presents exciting new directions for the field, including increasing the value of otherwise pervasive materials, uncovering entirely new material properties, and a viable path to upcycle post‐consumer plastic waste. Abstract : Hot commodities : This Review discusses the historical significance of and contemporary advances in the C−H functionalization of commodity polymers. Exciting new directions for the field are presented, including uncovering new material properties and upcycling post‐consumer plastic waste.